Why is farming important for rural livelihood security in the global south? COVID-19 and changing rural livelihoods in Nepal's mid-hills - Khatri, Dil; Marquardt, Kristina; Fischer, Harry; Khatri, Sanjaya; Singh, Devanshi; Poudel, Dilli Prasad (Frontiers in Human Dynamics, 2023)
Over the last three decades, Nepal has experienced a rapid transition in rural livelihoods, from largely subsistence farming to more diversified off-farm employment and remittances. Despite this, subsistence farming continues to be a central part of rural production. Why does farming persist in the face of other, more remunerative, off-farm employment options? In this article we argue that subsistence food production continues to be important for rural livelihood security by providing food needs from farming, thus helping households to cope with uncertaCOVID-19n off-farm employment and international labour migration. Taking the COVID 19 pandemic as an example of a high level of livelihood stress, the paper provides insights and further explanations on the logic of maintaining subsistence food production as part of rural household livelihood security. Drawing on in-depth qualitative study, complemented with a quantitative survey from 8 villages in rural Nepal, we examine the impact of the pandemic on farming and off-farm activities and explore the reasons behind peoples’ choice of livelihood strategies and how these vary between different social groups. We show that there was only limited impact of the dramatic disruptions caused by the global pandemic on subsistence farming, however, it brought substantial challenges for emerging semi-commercial farming and off-farm incomes, including both local and migratory wage labor. During the pandemic, people increased their reliance on locally produced food, and subsistence farming served as a critical safety net. Our analysis underscores the continued importance of subsistence production amidst contemporary shifts toward off-farm employment among rural households. We also find a growing interest in semi-commercial farming among farmers with better access to land who seek state support to develop such production. This suggests that it is important for agricultural development policy to recognize and support subsistence farming alongside emerging commercial agriculture production as an integral foundation of future farming and rural livelihood security.